Is There Evidence for Neurocognitive Dysfunctions in Patients with Postnatal HIV Infection? A Review on the Cohort of Hemophilia Patients - Riva, Silvia; Cutica, Ilaria; Pravettoni, Gabriella (Frontiers in Human Neuroscience, 2014)
The debate regarding neurocognitive functions in the early stages of HIV infection is still ongoing; different studies have reached contrasting conclusions, probably because many of them take into account different cohorts of patients. A main distinction is between HIV seropositive patients infected perinatally, and those infected postnatally. The aim of this paper is to review results on neurocognitive dysfunctions and other types of neurological involvement in a specific cohort of HIV+ patients infected postnatally: haemophilia patients. Such a review is relevant, as HIV seropositive patients infected postnatally are understudied with respect to patients infected perinatally, and as the results of the few studies aiming at comparing them are contrasting. Taken together, the eleven studies reviewed suggest the presence of both long-term neurocognitive dysfunctions and neurological alterations, such as the presence of atrophic changes and lesions in the white matter. The current review may offer new research insights into the neurocognitive dysfunctions in HIV patients, and on the nature of such dysfunctions.